Involvement of the Mitochondrial Protein Tyrosine Phosphatase PTPM1 in the Promotion of Conidiation, Development, and Pathogenicity in Colletotrichum graminicola - Shaowei Wang; Guihua Li; Guihua Li; Yi Wei; Yi Wei; Gang Wang; Yuejia Dang; Penghui Zhang; Shi-Hong Zhang; Shi-Hong Zhang (Frontiers in Microbiology, 2021)
The phosphorylation status of proteins, which is determined by protein tyrosine kinases (PTKs) and protein tyrosine phosphatases (PTPs), governs many cellular actions. In fungal pathogens, phosphorylation-mediated signal transduction has been considered to be one of the most important mechanisms in pathogenicity. Colletotrichum graminicola is an economically important corn pathogen. However, whether phosphorylation is involved in its pathogenicity is unknown. A mitochondrial protein tyrosine phosphatase gene, designated CgPTPM1, was deduced in C. graminicola through the use of bioinformatics and confirmed by enzyme activity assays and observation of its subcellular localization. We then created a CgPTPM1 deletion mutant (ΔCgPTPM1) to analyze its biological function. The results indicated that the loss of CgPTPM1 dramatically affected the formation of conidia and the development and differentiation into appressoria. However, the colony growth and conidial morphology of the ΔCgPTPM1 strains were unaffected. Importantly, the ΔCgPTPM1 mutant strains exhibited an obvious reduction of virulence, and the delayed infected hyphae failed to expand in the host cells. In comparison with the wild-type, ΔCgPTPM1 accumulated a larger amount of H2O2 and was sensitive to exogenous H2O2. Interestingly, the host cells infected by the mutant also exhibited an increased accumulation of H2O2 around the infection sites. Since the expression of the CgHYR1, CgGST1, CgGLR1, CgGSH1 and CgPAP1 genes was upregulated with the H2O2 treatment, our results suggest that the mitochondrial protein tyrosine phosphatase PTPM1 plays an essential role in promoting the pathogenicity of C. graminicola by regulating the excessive in vivo and in vitro production of H2O2.